The EVA as predicted Eq 2, the linear mixed effects model. - Mohammed Safayet Arefin (22683505) (2025)
The model parameters are shown: the global intercept (a_overall), slope (b), and the intercept offsets for each participant (a_part) and environment (a_Real, a_AR, a_VR). x marks the intercept of each participant, a_overall + a_part. Note the large variation in participant intercepts (a_part) compared to environment intercepts (a_Real, a_AR, a_VR). Also see Fig 9.